Finger Painting Pada Pembelajaran Seni Budaya dan Keterampilan - Delia Meriska; Hasnawati Hasnawati; Herman Lusa (Universitas Bengkulu, 2021)
This study aims to describe the process of making and the results of finger painting work in class II B Culture and Skills Arts (SBK) subjects at SDN 87 Bengkulu City. This type of research is qualitative descriptive research, with participant observation techniques. The subjects of this study were all students of class II B SDN 87 Bengkulu City, amounting to 27 students and the work of finger painting. The selection of subjects in this study was based on purposive sampling. The research instrument is a human instrument, using observation guidelines, interview guidelines and guidelines for the work. Data collection techniques in the form of observation, interviews and documentation. Data analysis of the process of making the work is done by examining the data then reduced, displaying and drawing conclusions. Data analysis of the work will be discussed by looking at the elements and principles of existing art. The results of the research are (1) The process of making finger painting artwork begins with preparing tools and materials such as paperboard, coloring pulp, newspaper, plastic for the dye pulp foundation. Next is the execution of the work. Then the last finishing. (2) Results of finger painting art work that students make have included elements and principles of fine art. The elements that are contained are dots and spots, lines, fields, colors, shapes, textures and light darkness. Then, the principle in finger painting artwork has fulfilled the principles of art, namely the principle of unity, proportion, balance, rhythm, emphasis and harmony.